Moral enhancement: A critique based on utility - Παπακωνσταντίνου (Κyriaki Papakonstantinou), Κυριακή (Bioethica, 2018)
Recent rapid advances in the field of life sciences such as medicine, biotechnology, genetics, biology and neurosciences alongside cognitive sciences raise serious moral concerns. Among the key issues is the one that concerns the way our genetic structure as well as our brain chemistry influences our behaviour. Questions are continually emerging, regarding the genetic basis of behaviour and its manipulation, leading eventually to the enhancement, moral, psychological, cognitive etc. of the human being through science. One of the most controversial issues in bioethics is the possibility of using our knowledge to biologically manipulate traits which have genetic basis as well as to strategically influence people's moral dispositions and behaviour by biomedical means in order to enhance moral behaviour. Therefore, in this article, Ι will try to evaluate the moral enhancement and its importance as set out in the article by Julian Savulescu and Ingmar Persson “Moral Enhancement, Free Will and the God Machine”, while at the same time exploring whether the implementation of such a challenge can be beneficial.